3D printing of semicrystalline polypropylene: towards eliminating warpage of printed objects - Bachhar, Nirmalya; Gudadhe, Aniket; Kumar, Anil; Andrade, Prem; Kumaraswamy, Guruswamy (Bulletin of Materials Science, 2020)
Fused filament fabrication (FFF) is an extrusion-based 3D printing technique for thermoplastic polymers. In this technique, molten polymer is extruded through a print nozzle and is laid down layer by layer to build up the printed object. Currently, FFF is used primarily to print amorphous or low-crystallinity polymers, such as acrylonitrile butadiene styrene copolymer (ABS) or polylactic acid (PLA). Printing of semicrystalline polymers, such as polyethylene or polypropylene remains particularly challenging. During FFF of semicrystalline polymers, large thermomechanical stresses are generated when the polymer solidifies on cooling. These stresses result in warpage of the printed part. Here, we analyse the factors that influence stresses generated during FFF 3D printing of a commercial semicrystalline polymer, isotactic polypropylene. We investigate the effect of height of the printed object on part warpage, as well the effect of infilling during printing. We demonstrate that the stresses generated during FFF can be substantially decreased by incorporation of a `brim', viz. a thin layer at the base of the printed object, and by adhering the brim to the print substrate using common polyvinyl acetate-based glue. We systematically investigate the effect of the brim size on the warpage of the printed object. We support our experimental findings with finite element method (FEM) simulations that explain the mechanism of stress buildup during printing. The trend in stresses calculated in the FEM simulations parallel the warpage measured in the experiments. Thus, this work represents an important methodological advance towards warpage-free FFF printing of semicrystalline polymers.
Keywords: 3D printing; polypropylene printing; warpage